Knowledge, Attitude, and Practices Regarding Monkeypox among Final-Year Dental Undergraduate Students, House Surgeons, and Dental Practitioners in Ernakulam District, Kerala - Mallika Balagopal; Shiney Sara Alexander; S. Jesnim; Jesline Merly James; Priya Babu; C. P. Athira; Suneesh Kuruvilla; R. Subramaniam (Journal of Nature and Science of Medicine, 2025)
Introduction: Monkeypox is a zootonic virus, belonging to the orthopoxvirus genus of the pox viridae family. Recently, the world is witnessing a sudden rise in the number of monkeypox cases. The clinical presentations of monkeypox are similar to that of smallpox. Dental practitioners have a thorough knowledge of the anatomy of the face and oral cavity and thereby can help in the early diagnosis of monkeypox. The objective of this study is to focus on the knowledge, attitude, and practices (KAP) of dentists in Ernakulam district, Kerala toward monkeypox. Methodology: A cross-sectional questionnaire-based study was conducted among clinical dental students and dental practitioners in Ernakulam district. The questionnaire was divided into two parts: Part I and Part II. The first part consisted of personal details. The second part consisted of 13 close-ended questions and one open-ended question on KAP on the distribution, clinical presentation, investigations, and management of monkeypox. Results: Among a total of 266 dentists and final-year dental students, 262 gave their consent to participate. The response rate was 98.49%. About 81.6% (n = 217) of participants were aware of monkeypox as a disease and about 73% (n = 171) of the participants stated that the disease is prevalent in African countries. Nearly 74% (n = 197) of the respondents were aware that there are cases of monkeypox reported in India. About 39.1% (n = 104) of the dentists have reported that dentists can help in the diagnosis of monkeypox. About 30.11% (n = 53) of the participants reported that they will refer a suspected case to the nearest hospital or general physicians and 11.36% (n = 20) participants were not sure of the proper treatment. Conclusion: While most of the participants were aware of the basics of the disease, it also showed how there was a significant knowledge gap, when it came to the management of monkeypox. This study also showed there is a need for increased awareness of monkeypox.